2018
DOI: 10.1161/circulationaha.118.035648
|View full text |Cite
|
Sign up to set email alerts
|

Small GTP-Binding Protein GDP Dissociation Stimulator Prevents Thoracic Aortic Aneurysm Formation and Rupture by Phenotypic Preservation of Aortic Smooth Muscle Cells

Abstract: -Thoracic aortic aneurysm (TAA) and dissection (TAD) are fatal diseases, which cause aortic rupture and sudden death. The small GTP-binding protein GDP dissociation stimulator (SmgGDS) is a crucial mediator of the pleiotropic effects of statins. Previous studies revealed that reduced force generation in AoSMCs causes TAA and TAD. -To examine the role of SmgGDS in TAA formation, we employed an angiotensin II (AngII, 1,000 ng/min/kg, 4 weeks)-induced TAA model. -33% mice died suddenly due to TAA rupture, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 63 publications
0
36
0
Order By: Relevance
“…Nogi M et al reported that disruption and degradation of medial elastic lamina in the ascending aorta were more severe in ApoE −/-SmgGDS ± mice compared with ApoE −/mice after AngII infusion for 4 weeks. However, there was no significant difference in the disruption and degradation of the medial elastic lamina in the abdominal aorta between the two genotypes after AngII infusion [29]. Therefore, it was no surprising to find that TRPV1 expression was decreased in AngII-induced abdominal aortic aneurysm mouse models.…”
Section: Discussionmentioning
confidence: 96%
“…Nogi M et al reported that disruption and degradation of medial elastic lamina in the ascending aorta were more severe in ApoE −/-SmgGDS ± mice compared with ApoE −/mice after AngII infusion for 4 weeks. However, there was no significant difference in the disruption and degradation of the medial elastic lamina in the abdominal aorta between the two genotypes after AngII infusion [29]. Therefore, it was no surprising to find that TRPV1 expression was decreased in AngII-induced abdominal aortic aneurysm mouse models.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, Ang II induced loss of the contractile phenotype and gain of the synthetic phenotype as evidenced by decreased ACTA2 and MYH11 expression and increased SPP1 and vimentin expression in mAoSMCs, suggesting a phenotypic switch. Induction of AoSMC switching from a normal contractile to a synthetic phenotype with mutations of ACTA2 and MYH11 promotes secretion of MMPs, inflammatory cytokines and growth factors, resulting in ECM degradation and aortic wall weakening and thus TAD rupture (Liu et al., 2017; Nogi et al., 2018). Destruction of the elastin‐contractile unit causes impaired function of AoSMCs, leading to aortic wall dilatation and failure (Nogi et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we evaluated the levels of cytosolic ROS after treatment with the 25 analogs and found that the analog b significantly reduced ROS in PAH-PASMCs ( Figure 2G). Because we previously confirmed that intracellular ROS in PAH-PASMCs is increased compared with control PASMCs 19 and higher levels of cytosolic ROS are mechanistically involved in the proliferation of PAH-PASMCs, 19,27,28 we used the analog b in the following experiments in vivo and in vitro.…”
Section: Development Of Celastramycin Analogues and Their Structure-amentioning
confidence: 99%